Breathe better: an evaluation of a hospice group to support people with end-stage chronic obstructive disease (COPD). Issue 3 (1st September 2016) - Middleton-Green, Laura; Lawson, George; Rayment, Clare
Abstract : Background: The Breathe Better group (BBG) has been running in the hospice in 2008. It aims to reduce dyspnoea, improve quality of life and mastery of illness for patients with end stage COPD using four methods: education, exercise, pharmacological management and individual consultations. We aimed to ascertain the short and long-term impact of the BBG. Method: A retrospective longitudinal study was performed on patients referred between 2010 and 2013. Data were collected on shuttle walk distance, mastery, Hospital Anxiety and Depression Scores (HADS), advance care planning (ACP), and mortality. Outcomes were analysed using a paired t-test. Results: Data from 56 patients was analysed. Mean shuttle walk distance increased by an average of 10.8 m which was statistically significant (p = 0.05). Total HADS score improved by 2 points. 65% of patients had an ACP after the group, compared with 24% prior to commencement. 76% patients died with 2 years. Place of death was as follows: (n = 45) Care home 11%, Home 7%, Hospital 38%, Hospice 31%, Not recorded 13%. There was a significantly increased rate of hospice death compared to regional and national COPD data and a proportionate reduction in hospital deaths. Discussion: Results suggest that BBG improved shuttle walk distance and recording of future health decisions and may influence place of death. Implications: BBG improved patients' exercise tolerance and ACP. From a public health perspective, the success of BBG suggests other hospices may wish to consider pilot schemes. A larger study with a defined control group (patients choosing not to attend) will allow more accurate comparison. Improved record-keeping is required to enhance data accuracy and reduce missing data. References: Chin C, Booth S.Managing breathlessness: a palliative care approach. Postgrad Med J 2016 Purdy S. Avoiding hospital admissions: What does the evidence say . London: The King's Fund; 2010 Spathis A, Booth S. End of life care in chronic obstructive pulmonary disease: in search of a good death. Int J Chron Obstruct Pulmon Dis 2008;3 (1):11–29